Preços exploratórios: a operacionalização do conceito, o tratamento da matéria no Brasil e a advocacia da concorrência - Isadora de Castro Silva (2017)
The purpose of this dissertation is to examine whether the concept of exploitative prices can be implemented given the wide divergences that cross the subject. In this sense, an exploratory methodology will lead the research due to its function of highlighting characteristics, perceptions and definitions. A descriptive methodology will also be used, responsible for the decomposition of a legal problem in its various aspects and levels, which will pave the way for a deeper investigation. In this research, besides the analysis of the pertinent controversies, cases appreciated by the Brazilian System of Defense of the Competition will be analyzed, which will involve an empirical study. Finally, as a consequence of the insufficiency of the traditional solutions presented to the problem, competition advocacy will be investigated as an alternative form of action against the issue object of this work. To this end, the exploratory methodology will be used again.